Biological Drugs Used in Veterinary Medicine Against Infectious Diseases and Their Types - Ilkhomovich, Klichov Odil; Sarsengaliyevna, Nurgaliyeva Janar; Nuriddinovich, Ergashev Najmiddin (European Journal of Life Safety and Stability (2660-9630), 2021)
Infectious diseases are now being prevented through the use of biological drugs in veterinary practice. If biological drugs are not used in a timely manner in veterinary practice, animals on farms can become infected with infectious diseases and cause great economic damage, so by using biological drugs, we can protect the health of animals and humans.